RANCANG BANGUN SISTEM INFORMASI PENJADWALAN DAN PENILAIAN PRAKERIN BERBASIS WEB DI SMK NEGERI 1 BANGKINANG - Nur Azizah; Willyansah; Rahmad Al Rian (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study develops a web-based information system to automate the scheduling, document management, and assessment of Industrial Work Practices (Prakerin) at SMK Negeri 1 Bangkinang, which were previously managed manually, making the process inefficient and error-prone. The research method used is Research and Development with the Waterfall model, consisting of analysis, design, implementation, testing, and maintenance stages. The system was built using the Laravel framework and provides integrated features for registration, scheduling, data management, and student assessment. Black Box testing showed that all features functioned properly, while usability testing with 26 respondents resulted in a score of 83.08%, categorized as “very feasible.” These results indicate that the developed system is effective, feasible to use, and able to improve efficiency, accuracy, and transparency in managing Prakerin activities at the school.